2008
DOI: 10.1007/s00468-008-0230-y
|View full text |Cite
|
Sign up to set email alerts
|

De novo organogenesis and plant regeneration in Pongamia pinnata, oil producing tree legume

Abstract: Role of Thidiazuron (TDZ) in inducing adventitious organogenesis in Pongamia was studied. TDZ at different concentrations (0, 0.45, 2.27, 4.54, 6.71, 9.08, 11.35, 13.12 and 22.71 lM) were used for induction of caulogenic bud formation in deembryonated cotyledon explants. Each cotyledon was cut into three segments and identified as proximal, middle and distal. Duration of TDZ exposure, influence of the segment and orientation of the explant were studied. TDZ at 11.35 lM concentration was optimum for the induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Other studies have provided data to explain the highly prolific nature of the proximal region of cotyledon explants. Sujatha et al (2008), using a direct shoot organogenesis protocol, tested three cotyledon segment types (proximal, middle, and distal) of Pongamia pinnata, a tree legume. This study concluded that the proximal cotyledon section, followed by the middle and distal sections, was most responsive in terms of producing shoot buds.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have provided data to explain the highly prolific nature of the proximal region of cotyledon explants. Sujatha et al (2008), using a direct shoot organogenesis protocol, tested three cotyledon segment types (proximal, middle, and distal) of Pongamia pinnata, a tree legume. This study concluded that the proximal cotyledon section, followed by the middle and distal sections, was most responsive in terms of producing shoot buds.…”
Section: Resultsmentioning
confidence: 99%
“…Regeneration from cotyledon explants has been reported in several taxa [21][22][23][24]36,37] but it has been recorded in only a few species belonging to Citrus genus: adventive embryos formation in Citrus reticulata Blanco (Nagpur mandarin) and C. jambhiri Lush. (Rough lemon) [5], indirect somatic embryogenesis in C. reticulata "Local Sangtra" [38] and indirect shoot regeneration in C. grandis (L.) Osbeck (pummelo) [32,39].…”
Section: Resultsmentioning
confidence: 99%
“…Organogenesis from cotyledons was successfully obtained in Pongamia pinnata (L.) [21], Glicine max (L.) Merril [22], Dalbergia sissoo Roxb. [23], Capsicum annum L. [24] and Citrullus lanatus (Thunb.)…”
Section: Introductionmentioning
confidence: 99%
“…3A). Complete regeneration through organogenesis was reported from de-embryonated cotyledon explants (Sujatha et al, 2008;B. Biswas, unpublished data).…”
Section: Pongamia Pinnatamentioning
confidence: 86%